Dietary fat intakes, lipid profiles, adiposity, inflammation, and glucose in women and men in the Framingham Offspring Cohort - Yiannakou, Ioanna; Yuan, Mengjie; Zhou, Xinyi; Singer, Martha R.; Moore, Lynn L. (Frontiers in Physiology, 2023)
The role of dietary fat in the evolution of cardiometabolic disorders is highly controversial. As both dietary intake and the development of cardiometabolic risk differ by sex, we evaluated sex-specific differences in the associations between dietary fats (saturated and unsaturated) and four key cardiometabolic risk factors—lipid profiles, body fat, inflammation, and glucose regulation. We included 2391 women and men aged ≥30 years in the prospective Framingham Offspring Cohort. Weight-adjusted dietary fats (saturated, monounsaturated, and polyunsaturated fats, including omega-3 and omega-6) were derived from three-day dietary records. Analysis of covariance was used to derive adjusted mean levels of all outcomes. In both men and women, intakes of saturated and monounsaturated fats were inversely associated with TG:HDL ratio (p<0.02 for both). In women, higher omega-3 and omega-6 PUFAs were also inversely associated with TG:HDL (p<0.05 for both), but for men, only omega-3 PUFAs were associated (p=0.026). All types of dietary fat were beneficially associated with larger HDL particle sizes in both men and women while only saturated and monounsaturated fats were associated with larger LDL particles in men. In addition, saturated and monounsaturated fats were associated with statistically significantly higher concentrations of HDL and lower concentrations of LDL and VLDL particles in both sexes, while polyunsaturated fat had favorable associations in women only. Saturated fat also had beneficial associations with three measures of body fat. For example, women with the highest (vs. lowest) saturated fat intake had a lower BMI (27.7 ± 0.3 vs. 26.2 ± 0.4 kg/m2, p<0.001); similarly in men (28.2 ± 0.3 vs. 27.1 ± 0.2, p=0.002). Unsaturated fats had beneficial associations with body fat in women only. Finally, omega-3 PUFAs among women were inversely associated with interleukin-6 levels. There was no association between dietary fat intake and fasting glucose levels in either women or men. In sum, we found no evidence of an adverse association between dietary fats and several surrogate markers of cardiometabolic health. This study suggests that different dietary fats may have divergent associations with cardiometabolic risk in women and men, perhaps owing to differences in food sources of the same dietary fats.